Colostral transmission of BTV-8 antibodies from dairy cows six years after vaccination. Issue 39 (18th September 2018) - Ayrle, Hannah; Mevissen, Meike; Kaske, Martin; Vögtlin, Andrea; Fricker, Raffael; Hoffmann, Bernd; Büttner, Mathias; Marinovic, Zlatko; Walkenhorst, Michael
Abstract: Bluetongue virus (BTV) antibodies were analysed in 27 Swiss calves born in 2016 at the age of 16–19 days using competitive enzyme-linked-immunosorbent-assay (cELISA) and virus neutralization test (VNT) (animal trial permission number: 75684). Obligatory documentation proved that 15 of 27 dams were BTV-8 vaccinated once or three times in 2008–2010. The offsprings of the non-vaccinated dams were seronegative. Two of three calves and 11 of 12 calves descending from dams who had been vaccinated one or three times, respectively, had BTV specific serum antibodies. As Switzerland is considered BTV-free from 2010 to 2016, it is likely that BTV-8 antibodies were transferred via colostrum. Furthermore, we confirmed neutralizing cross-reactivity of BTV-8 with BTV-4 antibodies as 5 samples positive for BTV-8 were also reactive with BTV-4 antibodies.